Comparison of continuous and twice‐daily infusions of cyclosporine A for graft‐versus‐host‐disease prophylaxis in pediatric hematopoietic stem cell transplantation. Issue 2 (12th October 2014) - Umeda, Katsutsugu; Adachi, Souichi; Tanaka, Shiro; Ogawa, Atsushi; Hatakeyama, Naoki; Kudo, Kazuko; Sakata, Naoki; Igarashi, Shunji; Ohshima, Kumi; Hyakuna, Nobuyuki; Chin, Motoaki; Goto, Hiroaki; et al.
<x xml:space="preserve">Abstract</x> Background Cyclosporine A (CsA) is used widely for graft‐versus‐host disease (GVHD) prophylaxis in hematopoietic stem cell transplantation (HSCT); however, the optimal schedule of its administration has not been established. Although comparative studies of adult patients undergoing HSCT have demonstrated enhanced efficacy and safety of twice‐daily infusion (TD) compared with continuous infusion (CIF) of CsA, to our knowledge, similar studies have not yet been performed in pediatric groups. Procedure A self‐administered questionnaire was used to retrospectively compare the clinical outcome and incidence of CsA‐associated adverse events of 70 pediatric acute myelogenous leukemia patients who were receiving CsA by TD (n = 36) or CIF (n = 34) as GVHD prophylaxis for their first allogeneic HSCT. Results The cumulative incidences of grade II–IV acute GVHD and chronic GVHD, as well as the overall survival and event‐free survival rates, did not differ significantly between the TD and CIF groups; however, the incidence of severe hypertension was significantly higher in the CIF group than the TD group. Conclusions The analysis presented here indicates that TD and CIF administration of CsA have similar prophylactic effect on pediatric GVHD and suggest that TD is associated with a lower rate of toxicity than CIF in pediatric patients undergoing HSCT. Pediatr Blood Cancer 2015;62:291–298. © 2014 Wiley Periodicals, Inc.